Dentale erosjoner. Barn og unges kunnskap om dentale erosjoner - Isaksen, Marthe Berg; Andersen, Elisabeth Haug (UiT Norges arktiske universitet, 2017)
This study aimed to investigate the knowledge about dental erosion (DE) among children and adolescents 13 – 20 years. The study was based on a questionnaire regarding knowledge of DE, oral symptoms, soft drink consumption and oral hygiene habits, and was implemented at three different schools in Troms county: one occupational school (n=42) and one study specialized school (n=64) both in Sør-Troms 16-20 yrs, and one “youth-school” in Tromsø 13 yrs (n=116). The analyzes were done in SPSS using crosstabs and frequencies tables. In total 222 (n) questionnaires were answered at the three different schools. 51.8 % (n=115) of the students were boys and 48.2 % (n=107) were girls. Children and adolescents have in general little knowledge about DE. There were no significant differences when we compared age, sex and education level. The school that had most knowledge was the “study specialized school”, and the school with the poorest knowledge was the “occupational school”, although the “study specialized school” was the school that had the least amount of knowledge about etiology of DE. There were no significant differences regarding sex in our results. We found a positive correlation between consumption of soft drinks and age, with older boys having the highest consumption, and a negative correlation between oral hygiene and age.